2019
DOI: 10.1111/jdv.15425
|View full text |Cite
|
Sign up to set email alerts
|

HIDRAdisk: validation of an innovative visual tool to assess the burden of hidradenitis suppurativa

Abstract: Background Hidradenitis suppurativa ( HS ) is a chronic, relapsing, inflammatory skin disease characterized by painful inflamed nodules, recurrent abscesses and fistulas located in apocrine gland–bearing body sites. The negative impact of HS on patient's quality of life (QoL) has been reported to be greater than other dermatologic conditions as psoriasis and atopic eczema, and its improvement is an important goal in disease management. Nowadays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 21 publications
4
38
1
4
Order By: Relevance
“…We herein showed, although in a retrospective study from a single centre, that improvement in HS after adalimumab treatment measured with mSS significantly correlated with QoL evaluated by HIDRAdisk. These results are in line with a recent Italian multicenter study conducted on 140 HS patients which showed significant correlation between HIDRAdisk score and HS severity evaluated through Hurley stage and HS‐PGA . Moreover, similar to a previous study, we demonstrated that treatment led to the highest rates of improvement in HIDRAdisk items such as pain, smell and daily activities.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We herein showed, although in a retrospective study from a single centre, that improvement in HS after adalimumab treatment measured with mSS significantly correlated with QoL evaluated by HIDRAdisk. These results are in line with a recent Italian multicenter study conducted on 140 HS patients which showed significant correlation between HIDRAdisk score and HS severity evaluated through Hurley stage and HS‐PGA . Moreover, similar to a previous study, we demonstrated that treatment led to the highest rates of improvement in HIDRAdisk items such as pain, smell and daily activities.…”
Section: Discussionsupporting
confidence: 92%
“…However, in order to analyse all HS aspects, it is crucial to define the precise burden of the disease and to objectively evaluate the rate of HS improvement at baseline and after therapy. In this context, HIDRAdisk, a simple and innovative visual HS QoL instrument, has been recently psychometrically validated in Italy demonstrating to improve the management of HS once implemented in routine clinical practice . We herein showed, although in a retrospective study from a single centre, that improvement in HS after adalimumab treatment measured with mSS significantly correlated with QoL evaluated by HIDRAdisk.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations